Evaluation of nematode larval load on forage pastures at Philippine Carabao Center at University of Southern Mindanao (PCC at USM) - Molina, Elizabeth C.; Corpuz, Jed Marlowe G. (2009)
The study was conducted from November 2006 to July 2007 at the Philippine Carabao Center at the University of Southern Mindanao (PCC at USM) and at the CVM-USM Parasitology Laboratory. The main objective of the study was to evaluate the gastrointestinal nematode larval load on herbage from the forage pastures of PCC at USM. The pasture areas that were sampled had larvae of the common gastrointestinal nematodes that infest ruminants. Specifically, third-stage larvae of Trichostrongylus, Haemonchus, Cooperia, and Oesophagostomum were observed. Fluctuations in counts of infective larvae (L3s) of these parasites were noted from November 2006 to July 2007 and the highest larval load occurred in April. Trichostrongylus was the dominant nematode seen from the herbage.
Keywords: Gastrointestinal nematodes; Parasitology; Larval load; Infective larvae; Mindanao studies; Philippine Carabao Center